An experience with COVID-19 positive pregnant patients at a tertiary care center - Baser, Anshu; Gupta, Akriti; Sharma, Sunil; Kumar, Sushil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The Covid-19 pandemic is a global phenomenon. The lockdown imposed by the central and state governments, has also led to restriction of movement of patients thus reducing their access to antenatal care. Our hospital was officially declared as a Covid-19 centre as per government directives. The hospital has been managing Covid-19 positive patients as per guidelines. We here present the data of management of COVID-19 positive pregnant patients. Methods: A retrospective study. All COVID positive patients admitted to the obstetric unit of the hospital from 23 March 2020 to November 2020 were analysed. A total of 96 COVID positive patients were analysed. The patients were analysed for antenatal complications, complications during delivery, mode of delivery and neonatal complications. Results: There was only one patient with major complications associated with COVID. Most of the patients were either asymptomatic or had mild symptoms. There was only one maternal mortality. 23 out of the 89 antenatal cases required emergency caesarean section. The caesarean section rate was higher in COVID positive patients though the caesarean sections were done for obstetric indications only. Three neonates tested positive for the virus. 2 of the neonate required NICU admission. Conclusions: COVID-19 is a completely unprecedented situation. The aim of this study was to demonstrate that the effect of COVID-19 on pregnant women is minimal. There were only 2 patients with major complications. The COVID positive pregnant patients can be managed effectively with proper personal protective equipment and adherence to guidelines.